1994
DOI: 10.2105/ajph.84.9.1468
|View full text |Cite
|
Sign up to set email alerts
|

State family planning and abortion expenditures: their effect on public health.

Abstract: OBJECTIVES. This study examines whether state family planning expenditures and abortion funding for Medicaid-eligible women might reduce the number of low-birthweight babies, babies with late or no prenatal care, and premature births, as well as the rates of infant and neonatal mortality. METHODS. Using a pooled time-series analysis from 1982 to 1988 with the 50 states as units of analysis, this study assessed the impact of family planning expenditures and abortion funding on several public health outcomes whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 22 publications
4
32
0
1
Order By: Relevance
“…These types of measures would contribute to a more sophisticated and holistic understanding of how programmes impact the lives of women and their children. A review of the available literature identified only one article examining the association between publicly financed family planning care and this larger set of outcomes 14 . Future research should utilise stronger methodology to investigate the link between publicly subsidised family planning services, prenatal care patterns and negative birth outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These types of measures would contribute to a more sophisticated and holistic understanding of how programmes impact the lives of women and their children. A review of the available literature identified only one article examining the association between publicly financed family planning care and this larger set of outcomes 14 . Future research should utilise stronger methodology to investigate the link between publicly subsidised family planning services, prenatal care patterns and negative birth outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Of these eleven studies, six relied on within-subject analysis [7][8][9][10]16,17 while five integrated the use of separate exposure and comparison groups [11][12][13][14][15] , capitalising on the staggered implementation of publicly subsidised family planning programmes among states and the natural division of treatment and control groups formed through income-eligibility cut-offs. Of the five multi-group analyses, two employed a time series approach 14,15 and three relied on a cross-sectional, difference-in-difference design [11][12][13] . Based on study sample selection, response rate, measurement accuracy and validity and attention to confounding variables, all eleven reviewed studies received a quality rating of 'fair' on the US Preventive Services Task Force quality rating scale ( Table 1).…”
Section: Study Design and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Meier and McFarlane [15] examined per capita family planning expenditures, including all federal and state funds, between 1982 and 1988, using a pooled time series analysis, and found no association with teen birth rates. Moore et al examined state family planning expenditures per female aged 15e44 years using data for the years 1989e2007, using a time-varying effects model to identify variations over time in the relationship between these expenditures and teen birth rates.…”
Section: Access To Family Planningmentioning
confidence: 99%
“…However, one of these studies (Guldi [12]) also conducted analyses by subgroup for age, race, and gender and found that parental involvement laws were related to a lower birth rate for white minor teens but had no association with nonwhite minor teens, whereas Kearney and Levine's 2012 analysis found no association (discussed above). Alternatively, Meier and McFarlane [15] examined data using state fixed-effect methods and found that a higher funded abortion rate (the number of publicly funded abortions in the state per 1,000 women aged 15e44 years) was associated with lower teen birth rates. Additionally, using data from 1989 to 2007, Moore et al constructed a measure to assess the restrictiveness of state abortion laws.…”
Section: Access To Abortionmentioning
confidence: 99%